Prenatal enzymatic diagnosis of Krabbe disease (globoid-cell leukodystrophy) using chorionic villi. Pitfalls in the use of uncultured villi - Harzer, K; Schuster, I (Human genetics, 1989)
Sixteen pregnancies in families with children enzymatically diagnosed as having Krabbe disease (KD) were monitored for prenatal KD using the assay of galactosyl ceramide beta-galactosidase (GCG) in uncultured chorionic villi (CV), cultured CV, or cultured amniotic fluid cells (AFC). Prenatal KD diagnoses were made for 5 pregnancies on the basis of lower than 10% normal GCG activity in cultured CV or AFC. Uncultured CV were studied in 3 out of the 5 KD embryos, although the GCG activities of 14%-23% as compared with control villi were diagnostically inconclusive; the relatively high activities were considered to be caused by maternal GCG contamination of these very small villus samples. Although the villi from 6 of the other pregnancies yielded more conclusive results, the use of uncultured CV alone is not recommended for prenatal KD diagnosis, this material being subject to possible uncontrolled contamination with maternal enzyme.